The assessment of homogeneity of gel on polimetilsiloxan basis containing extracts of quince leaves and grapes waste products for its technology optimization and improvement - Кузнецова, Елена Васильевна; Буцька, Вікторія Євгеніївна; Тимченко, Олександр Геннадійович; Джан, Тетяна Віталіївна (ScienceRise: Pharmaceutical Science, 2016)
Aim. To optimize technology of gel on Polimetilsiloxan basis containing extracts of Quince leaves and Grapes waste products for high quality drug with optimal shelf life creation. Methods. Pharmaceutical technology (particles size study by microscopy), physical and chemical methods were used. Results. Technological parameters of gel preparation were described. Technology of gel on Polimetilsiloxan basis containing extracts of Quince leaves and Grapes waste products was chosen by research results. Microscopy pictures of the studied gel samples were obtained using microscopy analysis of the gel structure. The gel has a structure of free created rigid matrix, built after polycondensation processes of methyl silantriole and siloxane bounds between silicon atoms. It has been experimentally proven that the structure of the finished drug on Polimetilsiloxan basis containing extracts of Quince leaves and Grapes waste products, prepared at temperature of 60 oС and mixing speed 1500 rpm, consists on equally distributed microparticles having almost identical form and adjacent to each other more tightly. The chosen technological modes are characterized by better microstructure ordering compared to their analogues at using other process parameters. Gel samples have satisfactory values of physical and chemical parameters. Conclusion. Technological parameters for obtaining of gel on Polimetilsiloxan basis containing extracts of Quince leaves and Grapes waste products were determined and substantiated